Adaptation Strategies being followed by Paddy Growers towards Climate Change in Punjab State (Indian Journal of Extension Education, 2020)
The study was conducted in five agro climatic zones of Punjab. One district from each zone, three blocks from each district and further one village from each block and finally 10 farmers per village having experience of minimum fifteen years of paddy cultivation were selected randomly. Data was collected by using the interview schedule. Majority (91.21%) had adopted short duration crop varieties and 82.43 per cent farmers were availing weather forecasting services. More than three fourth of the respondents opined that by using laser land management practices like leaser leveler they mitigate the effect of climate change during paddy production, while 26.35 per cent by using resource conservation technologies, 28.37 per cent by adopting soil moisture conservation methods, 11.48 per cent by stopping the burning of crop residue and only 10.81 per cent by using insect pest management techniques mitigate the effect of climate on paddy production. More than half of the respondents suggested that resistance varieties to insects-pest and diseases should be developed.